The magic school bus gets cold feet : a book about warm- and cold-blooded animals - West, Tracey, 1965-; Cole, Joanna; Ruiz, Art (New York : Scholastic, 1997)
The students in Ms. Frizzle's class learn about warm- and cold-blooded animals when they take the Magic School Bus to Herp Haven to search for their missing lizard, Liz.
"From an episode of the animated TV series produced by Scholastic Productions, Inc. Based on The magic school bus books written by Joanna cole and illustrated by Bruce Degen"--T.p. verso.
3.9
K-3
K-3
Keywords: Reptiles -- Juvenile literature; Mammals -- Juvenile literature; Cold-blooded animals -- Juvenile literature; Reptiles; Mammals; Reptiles; Mammals